2007
DOI: 10.1016/j.tem.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

It's all about sex: gender, lung development and lung disease

Abstract: Accumulating evidence suggests that gender impacts the incidence, susceptibility and severity of several lung diseases. Gender also influences lung development and physiology. Data from both human and animal studies suggests that sex hormones may contribute to disease pathogenesis or serve as protective factors, depending on the disease involved. In this review, the influence of gender and sex hormones on lung development and pathology will be discussed, with specific emphasis on pulmonary fibrosis, asthma and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
284
1
22

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(318 citation statements)
references
References 69 publications
11
284
1
22
Order By: Relevance
“…Sex also affects airway inflammation and the prevalence and severity of many major lung diseases, including pulmonary fibrosis, asthma, and lung cancer. Data from both human and animal studies indicate that sex hormones might contribute to disease pathogenesis or serve as protective factors, depending on the disease involved [21]. Traditionally, COPD has been regarded a male-specific disease owing to the difference in the prevalence of smokers between the sexes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Sex also affects airway inflammation and the prevalence and severity of many major lung diseases, including pulmonary fibrosis, asthma, and lung cancer. Data from both human and animal studies indicate that sex hormones might contribute to disease pathogenesis or serve as protective factors, depending on the disease involved [21]. Traditionally, COPD has been regarded a male-specific disease owing to the difference in the prevalence of smokers between the sexes [22].…”
Section: Discussionmentioning
confidence: 99%
“…O predomínio de sintomas de asma e rinite no sexo feminino na adolescência tem sido relatado por outros autores 22,23,24 . Vários fatores já foram descritos para explicar esses achados, dentre eles, o menor calibre das vias aéreas, fatores hormonais e maior exposição a alérgenos específicos do gênero 24,25,26,27 . No presente estudo, observou-se também que as adolescentes tiveram significativamente maior risco de apresentar a comorbidade asma-rinite e asma-rinoconjuntivite, corroborando com o achado de uma taxa significativamente maior de tosse seca noturna no gênero feminino.…”
Section: Discussionunclassified
“…(12,21) The prevalence of wheezing is generally higher in males in the first decade of life-when the caliber of their airways is smaller than is that of the females-and the opposite is observed from puberty onward. (22) Studies have also indicated the influence of the female sex hormones in the expression of asthma, and some of that epidemiological evidence has emerged from natural models, that is, menstrual cycles, pregnancy and menopause. (23)(24)(25) In addition, greater contact with the medical professional due to gynecological problems or prenatal care would increase the opportunity to report other conditions-including asthma and allergiesamong female adolescents, who are also subject to gender-specific environmental exposure, such as exposure to cosmetic products.…”
Section: Discussionmentioning
confidence: 99%